(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: There are marked variations in the incidence of urinary tract stones in children worldwide. Unlike other pathologies, the incidence and nature of pediatric urolithiasis differ significantly from country to country. While the disease has been reported to be rather rare in some areas, it is still an endemic problem in developing countries. There is evidence that the incidence of nephrolithiasis is growing with data suggesting that the overall prevalence reaching 8.8 of the population and this is higher than previous data which recorded 5.2 prevalence of kidney stones. The major metabolic abnormalities include: hypercalciuria, hyperoxaluria, hypocitraturia, cystinuria, and hyperuricosuria. Hypercalciuria or hypocitraturia are the most frequently reported abnormalities in children. The classic adult presentation of acute, severe flank pain, which radiates to the groin is uncommon in children, particularly in children younger than 5 years. Although adolescents present similarly to adult patients, younger children have varied presentations including nonspecific pain localized to the abdomen, flank, or pelvis. In infants, symptoms of stones may be confused with colic pain. Macroscopic or microscopic hematuria can occur in up to 90% of children with urolithiasis. Imaging techniques are used to exclude or substantiate the diagnosis and to determine the size and location of a stone including assessment of the consequences of obstruction to the urinary tract and renal function. Knowledge of these parameters is necessary to plan therapy adequately. Kidney-Ureter-Bladder (KUB) The KUB film can only reveal radio-opaque calculi. Diagnostic sensitivity, and specificity of KUB is 69%, 82% respectively (40) Examination of the skeleton can provide evidence of other causes of pain (for example the vertebrae). The first goal of medical management should be directed toward control of the acute complications. Pain associated with the passage of a stone is often severe and should be treated promptly with narcotic analgesics (morphine sulfate) and/or nonsteroidal ant-inflammatory drugs (Ketorolac). If the patient has vomiting or unable to drink, parenteral hydration should be used to maintain a high urine flow rate. In the absence of oligoanuric renal failure or a complete obstruction, an intravenous infusion rate of 1.5 to 2 times maintenance is recommended. Agents that may promote the passage of stones and reduce symptoms (medical expulsive therapy), such as alpha-adrenergic blockers (tamsulosin) and calcium-channel blockers (nifedipine), have shown promising results in adults with distal ureteral calculi. ESWL remains the first line of treatment of renal stones in children (75) However, its scope is now being challenged for the reasons that there have not been any major improvements in ESWL technology to improve the ESWL outcome of renal stone management, and it has largely failed to keep pace and compete with the better outcomes now being reported from the newer MIS developments such as mini/micro PCNL